2018
DOI: 10.1177/0363546518810750
|View full text |Cite
|
Sign up to set email alerts
|

Coping With Anterior Cruciate Ligament Injury From Childhood to Maturation: A Prospective Case Series of 44 Patients With Mean 8 Years’ Follow-up

Abstract: Background: There is no consensus regarding the best treatment approach for skeletally immature children with anterior cruciate ligament (ACL) injuries. High-quality studies with long-term follow-up are lacking, and evidence to support decision-making is limited. Purpose: To evaluate functional and patient-reported outcome, surgical history and complications in young adults who sustained an ACL injury before the age of 13 years and were treated with active rehabilitation and the option of delayed ACL reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 47 publications
1
37
0
1
Order By: Relevance
“…Our results may help explain why other studies have identified similar low functional hop test “passing” rates within ACLR populations 11,14,43 and why a recent systematic review and meta-analysis identified that only 23% of patients post-ACLR are able to pass return-to-play assessments at a 90% LSI threshold. 42 Future research should seek to determine whether other factors such as strength or balance may affect hop test performance within young athletes and focus on examining hop test performance across a wider age range of healthy individuals.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Our results may help explain why other studies have identified similar low functional hop test “passing” rates within ACLR populations 11,14,43 and why a recent systematic review and meta-analysis identified that only 23% of patients post-ACLR are able to pass return-to-play assessments at a 90% LSI threshold. 42 Future research should seek to determine whether other factors such as strength or balance may affect hop test performance within young athletes and focus on examining hop test performance across a wider age range of healthy individuals.…”
Section: Discussionsupporting
confidence: 63%
“…Unfortunately, neither study included frequency counts of individual patients able to achieve a threshold of ≥90% LSI on the entire battery of tests, which limits our ability to make further comparisons between those data and the current study. Ekas et al 11 recently published a case series evaluating the functional abilities of a cohort of young athletes who sustained an ACL injury before the age of 13 years. Among this group of patients, the mean age at the time of injury was 11 years, and the average follow-up occurred 8 years postinjury, yielding a mean age of 19.1 years at time of testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clinicians advocate early ACL surgery to prevent knee instability, and subsequently, new injuries to the menisci and cartilage 17–21. Others advocate early active rehabilitation to improve muscle function and stabilise the knee, only recommending ACL surgery if knee instability persists despite high-quality rehabilitation, or in the presence of repairable meniscal injuries 14 22–24…”
Section: Introductionmentioning
confidence: 99%
“…11,12 On the other hand, rehabilitation programmes and satisfactory outcomes from nonoperative treatment were reported in Europe. 9,13 The primary objective of our study was to assess the evolution of treatment approaches to ACL tears among skeletally immature patients and to examine the variations among members of Pediatric Orthopaedic Society of North America (POSNA) and European Paediatric Orthopaedic Society (EPOS). The secondary objective was to determine the number, type and severity of growth disturbances correlated with surgical reconstruction of the ACL.…”
Section: Introductionmentioning
confidence: 99%